IN VITRO ANTIBACTERIAL ACTIVITY OF CEFADROXIL CAPSULES CONSUMED BY PATIENTS IN THE HOSPITAL - Mahfudz Mahfudz; Suharjono Suharjono; Isnaeni Isnaeni; Primadi Avianto (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2021)
Clinical use of cefadroxil, particularly in Bangka Tengah Hospital, is proven beneficial to overcome mild to moderate infections which especially occur in soft tissues such as skin, upper respiratory tract, pharyngitis, tonsillitis and urinary tract. For this reason, it is necessary to procure cefadroxil to be available enough for the treatment of cases of these diseases. The cefadroxil used by the Central Bangka Hospital was obtained from several pharmaceutical industries with different prices and distributions, due to the possibility that the active raw materials and ingredients had different origins, so there was concern that the microbiological quality would be different. Drug procurement is carried out using the e-catalog or non-e catalog method. This study aimed to examine the microbiological quality of six preparations (A, B, C, D, E, and F) in terms of their inhibitory activities against Gram-positive and Gram-negative bacteria. The bioassay was carried out by diffusion agar method using Escherichia coli ATCC 29522 and Staphylococcus aureus ATCC 29523 as the bacterial test, and nutrient agar as the test medium. The inhibitory activities were compared to cefadroxil standard for measuring the ratio potency. The results showed that all samples fulfilled USP 41 requirements with potential ratio of 90% to 120% and minimum inhibitory concentration of ≤ 8 ppm and ≤ 2 ppm against Escherichia coli and Staphylococcus aureus respectively. The potency ratios to cefadroxil standard were 95.9%, 99.1%, 100.0%, 96.7%, 96.2% and 98.2% against Staphylococcus aureus while the potency ratios of 95.6%, 99.3%, 103.8%, 97.1%, 95.7% and 100.4% were achieved against Escherichia coli for A, B, C, D, E, and F samples, respectively.